2009
DOI: 10.1021/jo900486w
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Entry to 9-Azabicyclo[3.3.1]nonane N-Oxyl (ABNO): Another Highly Active Organocatalyst for Oxidation of Alcohols

Abstract: A practical, three-step synthetic route to 9-azabicyclo[3.3.1]nonane N-oxyl (ABNO, 3), an unhindered, stable class of nitroxyl radical, has been developed. ABNO exhibits a highly active nature compared with TEMPO in the catalytic oxidation of alcohols to their corresponding carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 41 publications
0
69
0
Order By: Relevance
“…A 0.003 mol% catalyst loading was sufficient to complete the reaction with Nor-AZADO. Nor- AZADO also exhibited efficient catalytic activity in the oxidation of primary alcohol compared with TEMPO, although AZADO and 1-Me-AZADO also worked well in this case 42,43) ( Table 6). The operationally facile and scalable features in synthesizing ABNO and Nor-AZADO should make their use applicable in many types of alcohol oxidation.…”
Section: Catalytic Activities Of Abno and Nor-azadomentioning
confidence: 99%
“…A 0.003 mol% catalyst loading was sufficient to complete the reaction with Nor-AZADO. Nor- AZADO also exhibited efficient catalytic activity in the oxidation of primary alcohol compared with TEMPO, although AZADO and 1-Me-AZADO also worked well in this case 42,43) ( Table 6). The operationally facile and scalable features in synthesizing ABNO and Nor-AZADO should make their use applicable in many types of alcohol oxidation.…”
Section: Catalytic Activities Of Abno and Nor-azadomentioning
confidence: 99%
“…Their stability is believed to be derived from the inability to form a nitrone C ¼ N double bond to the bridgehead-an elegant application of Bredt's rule 22 . AZADO (5) has recently been shown to be a powerful oxidation catalyst and is now commercially available because of the efforts of Iwabuchi and co-workers [23][24][25] , who also reported a number of other nitroxides inspired by the same design concept. Unfortunately, the bridged bicyclic design is not universally applicable.…”
mentioning
confidence: 99%
“…Outstanding research regarding this objective has recently been made by Iwabuchi's group, who reported and commercialized a sterically less-hindered nitroxyl radical, 2-azaadamantane-N-oxyl (AZADO), as one of the highly active catalysts for various reactions, including alcohol oxidations. 39,40) Thus, we subsequently focused on the use of AZADO in our strategy. The alcohols 2a-c were hence treated with the catalytic system employing the same amounts of the adamatane reagent 1 (1.1×1/4 eq relative to the alcohols, which corresponds to 110 mol% active iodine(III) sites) and AZADO (10 mol%) combination.…”
mentioning
confidence: 99%